Alkali-activated mortars: porosity and capillary absorption. Issue 4 (12th March 2023) - Ka, Moussa; Hoffmann, David; Molez, Laurent; Lanos, Christophe
Abstract: Studies conducted on alkali-activated materials in late years attested that they could be a replacement to ordinary Portland cement (OPC). Nevertheless, their performances in aggressive conditions require profound investigations to evaluate the ability to the fluid transfer. This article assesses the pore structure of alkali-activated mortars produced using one-part metakaolin combined with ground granulated blast furnace slag and other-part using only alkali-activated ground granulated blast furnace slag. The pore characteristics of alkali-activated mortars were compared to those of OPC as a reference. Tests consist in the measurement of the porosity accessible to water, water absorption and sorptivity. The results revealed that the alkali-activated based metakaolin combined with ground granulated blast furnace slag have greater porosity, water absorption, sorptivity and rate of water saturated porosity than alkali-activated based ground granulated blast furnace slag and Portland cement mortars.